Ekphrasis: por um viés ecológico da criação musical contextualizado pela memória, pelo esquecimento e pela referencialidade - Onofre, Marcílio Fagner (2020)
This thesis aims to investigate the universe of compositional ideas, dealing with the use of ekphrasis as a creative resource, from which composers elaborate their musical works having as starting point artistic productions expressed in different media such as, for example, texts, paintings, engravings, sculptures, etc. Thus, if necessary, a process of trans-medialization, when an idea is transposed from one medium to another and accessed by memory and by a creative and transmedialized listening, which is launched towards the referenced work. During the course of this thesis, we will bring some examples and analyzes of musical works of the 20th and 21st centuries that, in some way, are related to ekphrasis and, therefore, served as a starting point for the compositional approach proposed here. In this research, we will discuss a creative model in which the act of composing is thought from an ecological perspective, and thus becomes rooted in different works of art creating collaborative relationships with interpreters and, more broadly, connects to the social context, political and geographic location. From this perspective, the composer interacts with different types of environments, whether endogenous or exogenous to the musical work. Finally, the particularities of each of the ten works composed in the light of the theoretical and conceptual assumptions created and developed during this research are presented.